Perceived Achievements and Challenges with Using the Blended Writing Feedback System Based on CEFR in China - Li, Ting; Aziz, Azlina Binti Abdul; Sulaiman, Nur Ainil Binti (Journal of Qualitative Research in Education, 2025)
This study examines Chinese undergraduate EFL learners’ perceptions of a Blended Writing Feedback (BWF) system aligned with the Common European Framework of Reference for Languages (CEFR), integrating automated feedback from Cambridge Write & Improve and detailed teacher comments. Thirty-seven third-year English majors participated in a 12-week writing module, with 32 submitting comprehensive reflection logs describing their experiences. An explanatory mixed-methods design triangulated in-depth thematic analysis with systematic CEFR score tracking. Findings indicated perceived gains in grammar accuracy, rhetorical organization, CEFR awareness, and writing confidence, supported by feedback literacy and self-regulated learning frameworks. Reported challenges included difficulty interpreting vague or conflicting feedback, emotional frustration from stagnant CEFR levels, and a growing over-dependence on teacher input for revisions. Quantitative results showed overall CEFR level improvement across tasks, though notable discrepancies emerged between perceived and actual progress. The study highlights both the pedagogical benefits and the emotional-cognitive complexities of CEFR-based blended feedback in EFL writing. Recommendations include targeted feedback literacy training, more coordinated feedback delivery, and localized CEFR adaptation to enhance student engagement and motivation. The findings contribute to a deeper understanding of how automated and teacher-mediated feedback can be successfully integrated in higher education writing instruction.